Tingkat Perkembangan Biologi Nematoda Puru Akar (Meloidogyne spp.) pada Berbagai Jenis Tanaman Famili Solanaceae - PUTU AYU FRAHMI NANDRIATI; I MADE SUDANA; I MADE SUDARMA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2020)
Level Developmental Biology Root Nematode (Meloidogyne spp.) On DifferentTypes of Plants Family Solanaceae Meloidogyne spp. is an important parasitic nematodes which attack many crops in Indonesia. One of the host plants that are favored by Meloidogyne spp. is familysolanaceae. Solanaceace plant widely cultivated in Indonesia because of higheconomic value and become an important food ingredient. Attacks Meloidogyne spp.makes losing a very high yield so that the necessity of controlling performed tosuppress the attack of Meloidogyne spp .. Control with nematicides is a fast andpractical way, but the impact on the environment to be unfavorable. Therefore,controlling use of technical culture by means of crop rotation using a crop that is lessfavored by Meloidogyne spp. be an environmentally friendly alternative to control.This research see the development of larval stages II to IV and adult nematodes at 1gram root and larval stage II at 300 grams of soil by using red pepper plant (Capsicumannuum L.), cayenne pepper (Capsicum frutecesns L.), eggplant (Solanum melongenaL .) and tomato plants (Lycopersicum esculentum Mill).